Effect of substrate temperature and Ga source precursor on growth and material properties of GaN grown by hollow cathode plasma assisted atomic layer deposition - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
GaN thin films grown by hollow cathode plasma-assisted atomic layer deposition (HCPA-ALD) at two different substrate temperatures (250 and 450 °C) are compared. Effect of two different Ga source materials named as trimethylgallium (TMG) and triethylgallium (TEG) on GaN growth and film quality is also investigated and reviewed. Films were characterized by X-ray photoelectron spectroscopy, spectroscopic ellipsometery, and grazing incidence X-ray diffraction. GaN film deposited by TMG revealed better structural, chemical, and optical properties in comparison with GaN film grown with TEG precursor. When compared on basis of different substrate temperature, GaN films grown at higher substrate temperature revealed better structural and optical properties. © 2016 IEEE.
Keywords: Atomic layer deposition; GaN; Low temperature growth